How clean is clean? Incremental versus radical technological change in coal-fired power plants - Klaus Rennings; Peter Markewitz; Stefan Vögele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
In the discussion on innovations for sustainable development, radical innovations are frequently called for in order that the transformation of society to a system perceived as sustainable can succeed. The reason given for this is the greater environmental efficiency of these innovations. This hypothesis is, however, not supported by empirical evidence. Against the background of a globally increasing use of coal-burning power plants and the environmental impacts to be expected, the hypothesis that radical innovations are superior to incremental innovations is reviewed on the basis of fossil fuel power plants. This paper examines the diffusion of incremental and radical innovations in the field of power plants and the basic obstacles with which these innovations were confronted. To give an example, Pressurised Pulverised Coal Combustion (PPCC) as a radical innovation and supercritical coal-fired power plants as an incremental innovation are compared. An ex-post analysis of the German R&D portfolio in the past three decades in the field of power plants environmentally shows that technologies which were radical innovations had great difficulties in becoming accepted by possible investors. The future potential of radical innovations in the field of power plant technology is to be regarded as relatively low, especially due to comparatively high cost-pressure, the reluctance of utilities to take risks and the temporal dynamics of technological progress facilitating incremental innovations on the basis of conventional reference technology. The conclusion for future R&D work in the sector of large-scale power plants is that an innovation is more likely to succeed the more it follows established technological trajectories. In the context of energy market liberalisation, hardly any radical innovations are expected in this field of technology. The findings of this paper may also be helpful in evaluating risks or probabilities of success of technologies being developed. As an example technological trajectories currently favoured in CO2 capture are discussed.
Keywords: Q01; Q55; O31; O33; 330; Radical innovations; incremental innovations; carbon capture storage; coal power plants; Kohlekraftwerk; Umwelttechnik; Innovation; Innovationsdiffusion; Technischer Fortschritt; Kohlenstoffsenke; Erfolgsfaktor; Deutschland